On Computation of Degree-Based Entropy of Planar Octahedron Networks. (9th March 2022) - Sun, Tian-Le; Ali, Haidar; Ali, Bilal; Ali, Usman; Liu, Jia-Bao; Ali, Parvez
Abstract : Chemical graph theory is the combination of mathematical graph theory and chemistry. To analyze the biocompatibility of the compounds, topological indices are used in the research of QSAR/QSPR studies. The degree-based entropy is inspired by Shannon's entropy. The connectivity pattern such as planar octahedron network is used to predict physiochemical activity. In this article, we present some degree-based entropies of planar octahedron network.